2021
DOI: 10.1007/s40843-021-1652-2
|View full text |Cite
|
Sign up to set email alerts
|

A new class of nitrobenzoic acid-based AIE photosensitizers for highly efficient photodynamic antibacterial therapy

Abstract: Photodynamic therapy (PDT) has been drawing more and more attention in the antibacterial field. Traditional photosensitizers (PSs) tend to aggregate in aqueous media, which reduces the generation of reactive oxygen species (ROS) and seriously affects the photodynamic efficacy. Many efforts have been made to prevent aggregation of traditional PSs. By contrast, aggregation-induced emission PSs (AIE-PSs) take advantage of aggregation to boost ROS generation and fluorescence intensity. However, the efficacies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The synthetic procedure of CPVBA and its derivatives ( CPVBAs ) is the same as that of TTVBA and its derivatives ( TTVBAs ) reported by us previously (Scheme ). Knoevenagel condensation of 5-(4-(9H-carbazol-9-yl)­phenyl)­thiophene-2-carbaldehyde and methyl-2-methyl-5-nitrobenzoate provided CPVBA as a red precipitate in 97% yield without purification. The following amidation of CPVBA with piperazine afforded CPVBP in 94% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic procedure of CPVBA and its derivatives ( CPVBAs ) is the same as that of TTVBA and its derivatives ( TTVBAs ) reported by us previously (Scheme ). Knoevenagel condensation of 5-(4-(9H-carbazol-9-yl)­phenyl)­thiophene-2-carbaldehyde and methyl-2-methyl-5-nitrobenzoate provided CPVBA as a red precipitate in 97% yield without purification. The following amidation of CPVBA with piperazine afforded CPVBP in 94% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Most reported antibacterial rates of AIE-PSs did not exceed 2.0 log 10 , except for a membrane-anchored AIE-PS called a TBD anchor, which was reported to be able to kill 3.0 log 10 of Staphylococcus aureus ( S. aureus ) at a concentration of 2 μM and kill 3.0 log 10 of Escherichia coli ( E. coli ) at 5 μM with a 15 J/cm 2 light dose . We recently reported that diphenylamine group-based AIE-PSs ( TTVBA and its derivatives) can efficiently kill 4.0 log 10 of S. aureus at 1 μM and 3.8 log 10 of E. coli at 5 μM with a 48 J/cm 2 light dose, and we also reported a nitrobenzoic acid-based AIE-PS ( TPA-3NBA ) that can eliminate 6.0 log 10 of S. aureus at 1 μM with a 48 J/cm 2 light dose . The relationship between the molecular design and antibacterial performance of AIE-PSs still needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed an AIE-PS based on nitrobenzoic acid (namely TTVBA , Scheme 1), which has a free carboxylic acid group and can be coupled with alkylated piperazine to enhance its broad-spectrum antibacterial activity. 35 Its fluorescence has not been quenched; furthermore, it has the largest fluorescence enhancement ever reported (increase 375 times) during the aggregation. In addition to antibacterial studies, we have good reasons to further explore the application of nitrobenzoic acid-based AIE-PSs with fluorescence, such as TTVBA , in tumor imaging and ablation.…”
Section: Introductionmentioning
confidence: 99%
“…35 As a noninvasive feature and controllability method, PDT treatment can overcome the side effects of traditional methods such as radiotherapy, chemotherapy, and surgical resection. [36][37][38] To achieve an efficient PDT process, photosensitizers (PSs) [39][40][41][42] with excellent reactive oxygen species (ROS) generation ability are highly desired. 43,44 In biologically relevant processes, however, the chemical structures, the physiological environments, [45][46][47] and the self-assembled forms [48][49][50] of PSs have a salient influence on the inherent properties including the ROS generation ability as well as the emission behaviors.…”
Section: Introductionmentioning
confidence: 99%